THE PORNOGRAPHIZATION OF IMAGINATION. SOME COMMENTS ON PORN STUDIES IN LITERARY RESEARCH - Regiewicz, Adam (Prace Polonistyczne, 2020)
The exploration of human sexuality at the end of the nineteenth century did not immediately stimulate the development of research in literary eroticism. Its development is associated not so much with the discoveries made by anthropologists as with the influence of the Nietzsche’s philosophy and Freud’s psychoanalysis. The theory of Dionysian culture with its concept of libido (which in times of the supremacy of high culture remains hidden in the language of literature) contributed to the first wave of erotic criticism. Decades later, its development was related to feminist criticism, followed by gender studies and homoerotic studies. What seems interesting in this context is the lack of reflection on the role of the audiovisual pornographic imagination in most contemporary literature. While porn studies is present in sociology, anthropology, and film studies, it is still absent from literary studies. The article presents the mutual influence of literature and pornographic cinema, showing the limitation of the traditional tools used in literary studies in the analysis of contemporary literary descriptions of sexual acts. It examines the reason for the lack of research on this topic, paying attention to the ethical and aesthetic consequences of changing this situation. Finally, it outlines the areas of interest that porn studies could help explore.